2011
DOI: 10.1021/mp200421k
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts Contribute to Melanoma Tumor Growth and Drug Resistance

Abstract: The role of tumour-stromal interactions in progression is generally well accepted but their role in initiation or treatment is less well understood. It is now generally agreed that rather than consisting solely of malignant cells, tumours consist of a complex dynamic mixture of cancer cells, host fibroblasts, endothelial cells, and immune cells that interact with each other and micro-environmental factors to drive tumour progression. We are particularly interested in stromal cells (for example fibroblasts) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 33 publications
5
102
1
1
Order By: Relevance
“…We have chosen human melanoma as a model system because the interaction between tumor cells and carcinoma-associated fibroblasts seems to be crucial for tumor growth and the development of drugs resistance (33). As shown by Flach and colleagues, melanoma cells stimulate the recruitment of fibroblasts and activate them by a so far unknown mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have chosen human melanoma as a model system because the interaction between tumor cells and carcinoma-associated fibroblasts seems to be crucial for tumor growth and the development of drugs resistance (33). As shown by Flach and colleagues, melanoma cells stimulate the recruitment of fibroblasts and activate them by a so far unknown mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Flach and colleagues, melanoma cells stimulate the recruitment of fibroblasts and activate them by a so far unknown mechanism. In turn, these activated fibroblasts contribute to melanoma progression by providing both structural and chemical support (33). Incomplete abolishment of tumor cells by a short duration of kinase inhibitor therapy led to a transient reduction of tumor cells that was counteracted by an accelerated regrowth of tumor cells supported by the large fibroblast population that remained posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…3D spheroids may be used as simple cancer cell line spheroids, co-cultures of cancer cells with other cell types (e.g. fibroblasts) within the spheroid (35) or as a culture for the maintenance of patient tissues (36).…”
Section: D Spheroid Modelsmentioning
confidence: 99%
“…In a 3D co-culture model Flach and colleagues (2011) found that melanoma spheroids could recruit and incorporate fibroblasts. The presence of the melanoma cell soluble factors that recruited the fibroblasts also increased the rate of wound closure as much as 38%, indicating an increase in the secretion of fibroblast associated factors 171 .…”
Section: Melanoma and The Tumor Microenvironmentmentioning
confidence: 95%
“…Myofibroblasts are larger and more spindle-like in composition than regular fibroblasts; they also typically divide faster and produce more ECM 159,[169][170][171] .…”
Section: Melanoma and The Tumor Microenvironmentmentioning
confidence: 99%